KAJIAN TENTANG INTERAKSIONISME SIMBOLIK - Nina Siti Salmaniah Siregar (Universitas Medan Area, 2016)
The basic idea of symbolic interaction theory states that the emblem or symbol of culture are learned through interaction, people give meaning to everything that will control their attitudes and behavior. To understand the interaction of symbolic (symbolic interactionism) is a way of thinking about the mind (mind), self (self) and society (society).By using sociology as a foundation, as well as teaching that when human interact with each other, they share the meaning for a certain period and for a specific action. George Herbert Mead is a figure who is seen as symbolic interaction builders understand this. He taught that the meaning comes as a result of interaction between people, both verbally and nonverbally. Through the actions and responses that occur, we give meaning to the words or actions, and therefore we can also understand an even in certain ways too, because people are assumed to a rise from interrelated conversations between individuals.